A Pilot Study to Increase the Efficiency of HIV Outreach Testing Through the Use of Timely and Geolocated HIV Viral Load Surveillance Data. Issue 3 (March 2018) - Jennings, Jacky M.; Schumacher, Christina; Perin, Jamie; Myers, Tanya; Fields, Nathan; Greiner Safi, Amelia; Chaulk, Patrick
Abstract : Background: Eliminating HIV transmission in a population necessitates identifying population reservoirs of HIV infection and subgroups most likely to transmit. HIV viral load is the single most important predictor of HIV transmission. The objective of this analysis was to evaluate whether a public health practice pilot project based on community viral load resulted in increases in the proportion of time spent testing in high viral load areas (process measure) and 3 outcome measures—the number and percent of overall HIV diagnoses, new diagnoses, and high viral load positives—in one mid-Atlantic US city with a severe HIV epidemic. Methods: The evaluation was conducted during three, 3-month periods for 3 years and included the use of community viral load, global positioning system tracking data, and statistical testing to evaluate the effectiveness of the pilot project. Results: The proportion of time spent outreach testing in high viral load areas (69%–84%, P < 0.001) and the overall number and percent of HIV positives ((60 (3%) to 127 (6%), P < 0.001) significantly increased for 3 years. The number and percent of new diagnoses (3 (0.1%) to 6 (0.2%)) and high viral load positives (5 (0.2%) to 9 (0.4%)) increased, but the numbers were too small for statistical testing. Discussion: These results suggest that using community viral load to increase the efficiency of HIV outreach testing is feasible and may be effective in identifying more HIV positives. The pilot project provides a model for other public health practice demonstration projects. Abstract : A pilot project in Baltimore City, Maryland, suggests that using community viral load to increase the efficiency of HIV outreach testing is feasible and may be effective in identifying more HIV positives.